Potential role of N6-methyladenosine modification in circular RNA biogenesis and function in the inflammatory responses - Heedoo Lee; Heedoo Lee; Leo Chen; Yang Jin (Frontiers in Molecular Medicine, 2025)
N6-methyladenosine (m6A) is the best-studied post-transcriptional RNA modification. It refers to the methylation in the N6 position. M6A exists universally from viruses to mammalian cells and is highly abundant in RNA polymerase II-transcribed, protein-coding transcripts and various non-coding RNAs. M6A RNA modification influences multiple physiological and pathological processes. This RNA methylation plays a role in the pathogenesis of many human diseases, including but not limited to hematopoietic, central nervous, and reproductive systems. One of the m6A-modified non-coding RNAs is the circular form of RNA. Circular RNA (circRNA) refers to a single-stranded RNA molecule with a circular structure that exists across a wide range of organisms, including eukaryotes and prokaryotes. Its unique circular structure is formed by the covalent closure between the 3′and 5′ends of the RNA molecule. This closed-loop structure prevents the circRNA from being degraded readily by the exonucleases, resulting in more stability compared to its linear RNA counterparts. CircRNAs have been reported to regulate gene expression, protein interaction, and RNA sponging. They play important roles in many human diseases. M6A modifications of the host gene mRNAs regulate the circRNA biogenesis. Furthermore, m6A modification of circRNA itself adds additional regulation of these complicated processes. This mini-review elaborates on recent advances in m6A modification on circRNA biogenesis and function, focusing on the role of circRNA m6A modification in the development of inflammatory responses.